Topical Application of a Collagen Mimetic Peptide Restores Peripapillary Scleral Stiffness Reduced by Ocular Stress - Lauren K. Wareham; Ghazi O. Bou Ghanem; Kristin L. Clark; Eric Schlumpf; Brian J. Del Buono; David J. Calkins (Pharmaceuticals, 2025)
Background: The biomechanical properties of ocular tissues are critical to physiological processes that span ocular development, aging, and disease. The structural integrity of these tissues is important in mediating how the eye responds to strain and stress that pose challenges to physiological homeostasis. In the posterior segment, the peripapillary sclera and lamina separate the intraocular chamber and the fluid-filled subarachnoid space. Degradation of each contribute to pathogenic progression in multiple conditions and are largely determined by the integrity and architecture of collagen fibers, especially type I collagen. Methods: We used atomic force microscopy to measure how stress induced by elevations in intraocular pressure impacts stiffness of the peripapillary sclera and glial lamina in the rat eye and whether changes in stiffness could be influenced by topical treatment of a reparative mimetic of type I collagen. Results: Four weeks of elevated intraocular pressure reduced Young’s modulus in peripapillary sclera and glial lamina, coincident with reduced anterograde transport along the optic projection to the brain. Reduction in tissue stiffness correlated with an increase in fragmented collagen. Topical application of collagen mimetic peptide during the period of elevation countered both. Conclusions: Collagen remodeling occurs in many ocular conditions that influence the peripapillary sclera and glial lamina, including glaucoma and myopia. Our results suggest that topical application of collagen mimetic peptides that intercalate with and repair collagen damaged by disease processes could serve to mitigate changes in tissue stiffness and integrity due to degraded collagen.